Sense Horizons between Garroni and De Mauro - De Palo, Marina (Aesthetica Preprint, 2022)
This essay intends to show how the points of contact between Garroni’s and De Mauro’s theoretical reflection are to be framed in the common need to provide an epistemology of meaning. De Mauro, in his dialogue with Saussure, and Garroni, in his melee with Kant, share a meta-theoretical point of view that examines metalinguisticity (which will lead to the notion of meta-operativity) and the determinate/indeterminate nature of language.